Religious perspectives on religious diversity - McKim, Robert. (Philosophy of Religion - World Religions, 2016)
Religious Perspectives on Religious Diversity addresses fundamental and controversial questions raised by religious diversity. What are members of religious traditions to say about outsiders, their views, and their salvific status? And what are they to say about the religions of outsiders - about, say, whether those religions are inspired or salvifically effective or worthwhile or legitimate? Discussion of some Muslim, Christian, and Jewish perspectives is combined with more methodological work. The authors of these ground-breaking and original, yet readable and accessible, essays include established scholars and younger scholars whose reputation is growing. Contributors are: Imran Aijaz, David Basinger, Paul Rhodes Eddy, Jerome Gellman, Mohammad Hassan Khalil, Eugene Korn, Daniel A. Madigan, Robert McKim, John Sanders, and Diego R. Sarrió Cucarella. \'Judaism, Christianity and Islam's attitudes to other religions are thoughtfully examined in this collection, both with fine historical sensibility as well as original constructive contributions from leading scholars in the field. A series of helpful meta-reflections follow on: typologies in theology of religions; the act of comparison between traditions; and a plea for informed tolerance when difference is confronted. A rare treat: an edited collection that is of uniformly high quality, throwing immense light on the subject. It will help specialists and undergraduate students approaching the subject of religious pluralism.\' - Professor Gavin D'Costa, University of Bristol, September 2016.